Deciphering the key operational factors and microbial features associated with volatile fatty acids production during paper wastes and sewage sludge co-fermentation. (January 2022) - Luo, Jingyang; Li, Yuxiao; Li, Han; Li, Yibing; Lin, Lifang; Li, Yi; Huang, Wenxuan; Cao, Jiashun; Wu, Yang
Graphical abstract: Highlights: PW/SS co-fermentation is feasible for VFAs yield, especially acetic acid. pH and PW/SS ratio are two critical factors in determining the VFAs production. Acidic pH is favor for carbohydrate metabolism while alkaline is better for protein. The metabolic functions related with VFAs production are significantly stimulated. The functional fermentative bacteria for VFAs biosynthesis are greatly enriched. Abstract: This work explored the feasibility of paper waste (PW)/sewage sludge (SS) co-fermentation for volatile fatty acids (VFAs) production, and disclosed its correlation with the key operational parameters ( i.e., pH and PW/SS ratio). The results indicated that the maximal VFAs was 251.55 mg COD/g TSS at optimal conditions, which was approximately 10-folds of sole SS fermentation. PW feeding contributed to the bioavailable substrates and C/N balance during co-fermentation process. The pH exhibited evident impacts on organics solubilization/hydrolysis, in which acidic pH was more beneficial for carbohydrates metabolism while alkaline pH was better for proteins. Under optimal operational conditions, the metabolic functions associated with VFAs production ( i.e., substrate membrane transport, intracellular metabolism and VFAs biosynthesis) were up-regulated. Moreover, functional microorganisms ( i.e., Saccharofermentans and Bacteroides ) responsible for VFAs generation were enriched. This work provided an innovative approach to recovery valuable products from biowastes, and in-depth understandings of microbial features in PW/SS co-fermentation systems.